Exact solution of a variety of X-ray probes in the Falicov-Kimball model with dynamical mean-field theory - Shvaika, A.M.; Freericks, J.K. (Condensed Matter Physics, 2012)
We examine the core-level X-ray photoemission spectroscopy (XPS), X-ray absorption near-edge spectroscopy (XANES) and X-ray emission spectroscopy (XES) in the Falicov-Kimball model by using the exact solution from dynamical mean-field theory. XPS measures the core-hole propagator, XANES measures the absorption of X-rays when the core electron is excited to an unoccupied electronic state of the solid and is not emitted, and XES measures the spectra of light emitted as electrons fill the core-hole state created via some form of X-ray excitation. These three spectra are closely related to one another and display orthogonality catastrophe behavior at T=0. We show an efficient way of evaluating these spectra at finite temperature, with a primary focus on the details of XANES. Дослiджуються рентґенiвськi спектри фотоелектронної емiсiї (XPS), передкрайового поглинання (XANES) та фотоемiсiї (XES) для моделi Фалiкова-Кiмбала, використовуючи точнi розв’язки теорiї динамiчного середнього поля. XPS вимiрює пропагатор дiрки йонного залишку, XANES — поглинання X-променiв, коли електрон йонного залишку збуджується в незаповнену електронну зону твердого тiла, i XES — спектр випромiненого свiтла при заповненнi електроном наперед створеної X-променями дiрки йонного залишку.
Всi цi три типи спектрiв тiсно пов’язанi мiж собою i проявляють особливостi типу катастрофи ортогональ-ностi при T = 0. Показано, як ефективно розраховувати такi спектри для скiнчених температур, зокрема з детальнiшим наголосом на спектри XANES.